Stakeholders' climate perception and adaptation in coastal Uruguay. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this article is to discuss the assessment and inclusion of stakeholders' perception, and citizen participation instances to implementing management options to deal with climate threats within the existing institutional framework in Uruguay.Design/methodology/approach – The approach being followed has different directional approaches and integrates them within a single assessment. First, a prescriptive climate change top‐down path. Second, stakeholders' perception is assessed within a bottom‐up risk‐management model. Third, institutional agreements, arrangements, and consensus are reached. Considering the need for agreed and effective options, the approach is customized and turned flexible enough to accept inputs from scientists, managers, and stakeholders.Findings – The co‐production of knowledge and the achievement of agreed and feasible options is achieved by means of a consultation process which results in adaptive co‐management agreements and collective decisions. This process is seen as both an empowerment of local actors and a multi‐stakeholder learning‐by‐doing experiment. This allows for both an increase in coping capacity to climate threats and facilitates long standing conflict resolution.Originality/value – Much literature discusses the importance of the role of social power in inclusive processes towards adaptation, and how difficult is ceding a genuine voice to stakeholders. The co‐production of knowledge is a way to achieve the rapprochement of scientists with institutional and community actors. Thus, the participatory process gives stakeholders responsibility for identifying their specific needs and priorities and helps to establish community ownership. Acknowledgements : The research was carried out within the project "Implementing Pilot Adaptation Measures to Climate Change in Coastal Areas of Uruguay" (www.cambioclimatico.gub.uy), UNDP URU 07‐G32. Funding under the Global Environment Facility (GEF) is gratefully acknowledged.